Attitudes of Teachers Relating to School Morale Atmosphere: Empirical Research - Elisa Zobbi (Pensa MultiMedia, 2022)
Commencing with the definition of school moral atmosphere, this essay presents first results of an empirical research which aims to investigate the attitudes of aspiring, in-training, and in-service teachers. The study was conducted by means of a questionnaire entitled, Che cosa è bene, che cosa è male. La scuola e la sfida dell'educazione morale, which involved 763 participants. These included 224 aspirating teachers who participated in pre-F.I.T. training programs at the Universities of Parma and Sassari, 397 in-training teachers who underwent training in Special Needs Education at the Universities of Messina and Parma, and 142 in-service teachers from the provinces of Messina, Reggio Emilia and Parma. Data analyses were conducted through factorial and cluster analyses. Results of the cluster analyses revealed three different attitudes of teachers: first, one generally institutional, a second, more undecided in nature, and a third, which was mostly communicative in nature.